Heteroleptic nickel complexes of a bulky bis(carbene)borate ligand. (1st December 2018) - Martinez, Jorge L.; Lee, Wei-Tsung; Pink, Maren; Chen, Chun-Hsing; Smith, Jeremy M.
Graphical abstract: A bulky diphenylbis(carbene)borate ligand provides access to heteroleptic nickel complexes. Abstract: Bis(carbene)borate ligand transfer to the nickel nitrosyl synthon Ni(NO)(PPh3 )2 Br provides the new nickel nitrosyl complex Ph2 B( t BuIm)2 Ni(NO)(PPh3 ). The solid state structure reveals a trigonal pyramidal nickel ion with a very long bond to the apical PPh3 ligand. The complex reversibly dissociates PPh3 in solution to afford three-coordinate Ph2 B( t BuIm)2 Ni(NO), with NMR data providing evidence for PPh3 binding at low temperatures. Ligand transfer to Ni(PMe3 )2 Cl2 provides the square planar complex, Ph2 B( t BuIm)2 Ni(PMe3 )Cl, which shows no evidence for rearranging to the form a homoleptic complex with two bis(carbene)borate ligands. This complex is a suitable synthon for the [Ph2 B( t BuIm)2 Ni] + fragment, as demonstrated by the synthesis of the π-allyl complex Ph2 B( t BuIm)2 Ni(η 3 -C7 H7 ). The π-allyl complex reacts with O2 to provide benzaldehyde and an unstable complex that is tentatively identified as the nickel(II) hydroxide [Ph2 B( t BuIm)2 Ni(μ-OH)]2 .